OPTIMASI PEMBERIAN PUPUK GRAMAFIX DALAM DEGRADASI CEMARAN MINYAK BUMI OLEH BAKTERI INDIGENOUS SECARA IN VITRO - Linda Safitri; Agung Suprihadi; Endang Kusdiyantini; Yeti Darmayati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Petroleum pollution has bad impact for life in marine ecosystems, particularly in coastal areas. One method of handling the pollution is bioremediation using bacteria that are able to degrade and utilize petroleum hydrocarbons as carbon source. One technique of bioremediation is biostimulation, that is the addition of nutrients that can improve the process of oil degradation by degrading bacteria. Nutrient slow-release fertilizer are used, one of which is Gramafix. The purpose of this study was to determine the optimal concentration of Gramafix in increasing degradation of petroleum contaminants by indigenous bacteria. Four concentrations of Gramafix as treatments are P1 (0,085 g), P2 (0,171 g), P3 (0,341 g) and P4 (0,682 g), as well as the negative control treatment (no fertilizer and bacteria) and positive control (with bacteria, without fertilizer). Observations were carried out four times, on 0, 7, 14 and 28 days of incubation. The parameters used are heavy oil using the gravimetric method, the total number of bacterial cells using Acridine Orange Direct Counting and environmental factors such as nitrogen contents, phosphorus contents, temperature, dissolved oxygen, pH and salinity. Analysis of the data using a completely randomized design (CRD) with ANOVA and Duncan test. The results showed the P3 can improve the process of oil degradation by bacteria that degrade the highest percentage of 65,91% in the 28 days of incubation, it also has more bacterial cells than other treatments. The result of this study is the addition of 0,341 g Gramafix is optimum for enhancing the degradation of petroleum hydrocarbons by degrading bacteria. Keywords: Pollution, petroleum, bioremediation, biostimulation, slow-release fertilizer.